2020
DOI: 10.1016/j.carbpol.2019.115451
|View full text |Cite
|
Sign up to set email alerts
|

Ethylcellulose nanoparticles as a new “in vitro” transfection tool for antisense oligonucleotide delivery

Abstract: Oil-in-water nano-emulsions have been obtained in the HEPES 20 mM buffer solution / [Alkylamidoammonium:Kolliphor EL=1:1] / [6 weight % ethylcellulose in ethyl acetate] system over a wide oil-to-surfactant (O/S) range and above 35 weight% aqueous component at 25ºC. The nano-emulsion with an O/S ratio of 70/30 and 95 weight % aqueous component was used for nanoparticles preparation. These nanoparticles (mean diameter around 90 nm and zeta potential of +22 mV) were non-toxic to HeLa cells up to a concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
12
1
Order By: Relevance
“…Therefore, efficient transfection can be achieved using optimized of polynucleotides, which allow compacting large DNA molecules and rechargi This allows genetic material to be recognized by the cell [27,28], pass through membrane by the endocytosis mechanism [29] and receive protection from biod tion. From this point of view, cationic surfactants are among the most prospective [30][31][32][33][34], including those bearing an imidazolium moiety [35][36][37][38]. Imidazoli phiphiles and DNA were documented to form sustainable nontoxic complexes tect from enzymatic degradation and provide a charge density sufficient f transport through the cell membrane [35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efficient transfection can be achieved using optimized of polynucleotides, which allow compacting large DNA molecules and rechargi This allows genetic material to be recognized by the cell [27,28], pass through membrane by the endocytosis mechanism [29] and receive protection from biod tion. From this point of view, cationic surfactants are among the most prospective [30][31][32][33][34], including those bearing an imidazolium moiety [35][36][37][38]. Imidazoli phiphiles and DNA were documented to form sustainable nontoxic complexes tect from enzymatic degradation and provide a charge density sufficient f transport through the cell membrane [35].…”
Section: Introductionmentioning
confidence: 99%
“…Further, DLS measures the hydrodynamic diameters of solvated micelles whereas TEM measures dried micelles. 12 The PEG chains in the outer domains of the micelles are hydrophilic and hold water molecules, which is reflected in the DLS measurements; hence, formulations with a higher content of grafted mPEG (B4, B5, and B6) are larger in size. All these formulations possessed net negative charge on their surfaces (−15 mV to −42 mV), which was due to the OH − groups on the PEG chains of the micelles.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, S. Leitner et al reported the development of EC nanoparticles as a new transfection tool for antisense oligonucleotide delivery. 12 The hydrophobic nature of EC has benefits in terms of sustained release for oral administration; however, its hydrophobicity is a hurdle preventing its use in parenteral administration, as its hydrophobicity activates the macrophages of the immune system. To overcome this, the structure of EC needs to be modified without sacrificing its desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers around the world are increasingly thinking smaller and smarter to solve some of the biggest problems in medicine with precise technologies, helping to open up new possibilities for nanomedicine and membrane technologies. Some of the most promising research work in nanomedicine is driven by a focus on nanomembranes which goes deeper into the engineering of functional systems at the molecular and atomic level [ 1 , 2 , 3 ], combining elements of material physics and molecular chemistry to derive unique properties that occur at the nanoscale level [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%